قطف الثمار وتجفيفها ببلاد المغرب في العصر الوسيط من خلال المصادر - هواري, موسى (جامعة الوادي - University of Eloued, 2022)
يتناول هذا المقال مرحلةً مهمةً من الموسم الفلاحي بالمغرب خلال العصر الوسيط، وهي مرحلة قطف ثمار الأشجار، من خلال المصادر، حيث يتعرض لأوقات القطف، وكيفياته ووسائله، انطلاقا من الإشارات القليلة التي وردت في المصادر، كما يتطرق لمسألة مهمةٍ وهي تجفيف بعض الثمار كالتين والعنب، من أجل تسهيل حفظها أو نقلها لأماكن بعيدةٍ من أجل بيعها، وهو أيضا يتعرض إلى تصبير الزيتون ببلاد المغرب، باعتبار هذه الشجرة كانت من أكثر الأشجار انتشارا ببلاد المغرب. This article deals with the issue of fruit picking in the Islamique Maghreb , In the medieval period, Through sources, Fruit picking is part of the farm business during the agricultural season,This research tries to reveal the timing and how it is taken , It is also subjected to drying some fruits, such as figs and grapes, In this article, we will also deal with drying fruits such as figs and grapes in order to store them or facilitate their transportation to remote places, It also deals with pickling olives for consumption and storage.
مقال
Keywords: الفلاحة - غرس الأشجار- قطف الثمار- تجفيف التين- تصبير الزيتون- المغرب; fruit picking - Islamique Maghreb - pickling olives - medieval period planting -- Fruit trees